2006
DOI: 10.1530/eje.1.02155
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin, but not a polymorphism in type II deiodinase, predicts response to paroxetine in major depression

Abstract: Objective: The determinants of response to antidepressant treatment in major depression are unknown at present. The aim of the present study was to establish whether response is predicted by Hypothalamus-Pituitary-Thyroid (HPT) axis parameters or by a recently discovered polymorphism in the enzyme type II deiodinase (DII), which catalyzes the production of T 3 in the brain. Design: We analyzed prediction of response to paroxetine treatment by calculating response rates per tertile of HPT-axis parameters and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…An alternative explanation, that relatively low T 3 levels may be caused by genetic variants in any of the 3 deiodinase genes, is intriguing. One recent study did not find an association between a polymorphism in type II deiodinase and response to paroxetine hydrochloride, 34 but further studies are needed to explore this issue.…”
Section: Commentmentioning
confidence: 97%
“…An alternative explanation, that relatively low T 3 levels may be caused by genetic variants in any of the 3 deiodinase genes, is intriguing. One recent study did not find an association between a polymorphism in type II deiodinase and response to paroxetine hydrochloride, 34 but further studies are needed to explore this issue.…”
Section: Commentmentioning
confidence: 97%
“…For example, a study investigating pituitary secreted hormones into the bloodstream, revealed that higher serum TSH significantly predicted response to paroxetine (Brouwer et al, 2006). Higher plasma fibrinogen levels were identified in non-responders compared to responders to mixed antidepressants (Martins-de-Souza et al, 2014).…”
Section: Treatment Response Prediction In Major Depressive Disordermentioning
confidence: 99%
“…Other D1 and D2 polymorphisms (D1-A1814G, D2-ORF a -Gly3Asp, and D2-Thr92Ala) did not show a relationship with therapeutic response in this study. Brouwer et al (45) reported that the Thr92Ala polymorphism was not associated with response rate to antidepressant therapy with paroxetine in 96 patients treated for major depression.…”
Section: Cognitive Function and Affective Disordersmentioning
confidence: 99%